2008
DOI: 10.1209/0295-5075/84/19001
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of superluminal γ-rays: Tachyonic flare spectra of quasar 3C 279

Abstract: The polarization of superluminal radiation is studied, based on the tachyonic Maxwell equations for Proca fields with negative mass-square. The cross-sections for the scattering of transversal and longitudinal tachyons by electrons are derived. The polarized superluminal flux vectors of dipole currents are calculated, and the power transversally and longitudinally radiated is obtained. Specifically, the polarization of the γ-ray spectrum of quasar 3C 279 is studied. Two flare spectra of this blazar at redshift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Observations of this quasar [249][250][251][252][253][254][255][256][257][258][259][260][261][262], which is at a distance of 3 billion of light years, showed that it con sists of two radio sources of different intensities that are receding from each other such that, according to estimates of [254,255,261,262], the velocity of their separation exceeds the speed of light by an order of magnitude. Several different explanations of this phe nomenon have been put forward.…”
Section: Optical Illusions Of Superluminal Motionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations of this quasar [249][250][251][252][253][254][255][256][257][258][259][260][261][262], which is at a distance of 3 billion of light years, showed that it con sists of two radio sources of different intensities that are receding from each other such that, according to estimates of [254,255,261,262], the velocity of their separation exceeds the speed of light by an order of magnitude. Several different explanations of this phe nomenon have been put forward.…”
Section: Optical Illusions Of Superluminal Motionsmentioning
confidence: 99%
“…For example, in [251,261] (see also review [252]), it was suggested that the motion of objects consisting of real tachyons is being observed. (It is interesting to note that hypothe ses of this kind are considered to the present day [253].) The authors of [259] even developed a theory of superluminal magnetic dipole radiation created by charged particles moving with ultrarelativistic veloci ties in the magnetic field of the quasar.…”
Section: Optical Illusions Of Superluminal Motionsmentioning
confidence: 99%
“…1 does not imply a low redshift, as there is no intergalactic absorption of the tachyon flux. Tachyonic γ-rays are not attenuated by cosmic background photons, as tachyons and photons can only indirectly interact via matter fields [28,29,31].…”
Section: Grbmentioning
confidence: 99%
“…The electron temperature can be inferred from the exponential cutoff, β = m/(kT ) or kT [keV] ≈ 511/β. We consider ultra-relativistic multi-component plasmas in the collisionless regime [27], in stationary non-equilibrium described by power law densities [28,29].…”
mentioning
confidence: 99%
“…[18], and the radio quasar 3C 279 (z ≈ 0.538, 2.4 Gpc) in ref. [19]. The curvature of these spectra is uncorrelated with distance.…”
mentioning
confidence: 92%